The drone threat to just war theory: responding to Braun. (December 2020) - Norris, Kristopher
In this response to Christian Braun's article in this journal, I argue that the rise of drone warfare against terrorism suggests the necessity of the presumption against war (not its limit) and use the issue to advance this broader debate within just war theory at a pivotal moment in the tradition.